Respuesta :
Answer:
U(t) = (48/45)(cos 7t - cos 8t) seconds
Explanation:
Weight = 6lb
K = 1lb/in or 12lb/ft
U'(0) = 0 ft
U''(0) = 0 ft/s
F(t) = 2 cos 7t lb
We know that, w = mg
Thus, m = w/g = 6/32 = 3/16 lb²/ft
Thus, the initial value problem cam be written as;
3u'' + 192u = 48 cos 7t
Since, u'(0) = 0 ft and u''(0) = 0 ft/s, the corresponding homogenous equation is;
3u'' + 192u = 0
With a characteristic of ;
3p² + 192p = 0
So, p = ±√(192/3)i = ±√64i = ±8i
This is a pair of conjugate roots and thus the solution is;
u(t) = c1cos 8t + c2sin8t
And the particular solution can be written as;
Y(t) = A cos 7t + B sin 7t
Now, let's plug Y(t) into the initial value problem;
3Y''(t) + 192Y(t) = 2 cos 7t
3(-49Acos 7t - 49Bsin 7t) + 192(A cos 7t + B sin 7t) = 48 cos 7t
Thus;
-147ACos 7t - 147BSin 7t + 192A cos 7t + 192B sin 7t = 48 cos 7t ;
45A Cos 7t + 45B Sin 7t = 48 cos 7t
By inspection,A = 48/45 and B=0
Hence, the particular solution is;
Y(t) = (48/45)cos 7t
The general solution will now be;
U(t) = Uc(t) + Y(t)
U(t) = c1 cos8t + c2 sin8t + (48/45)cos 7t
Mow, let's find c1 and c2 from the conditions in the initial value problem.
Thus ;
At u(0) =0;
0 = c1 cos 0 + c2 sin0 + (48/45)cos 0
So, c1 = 48/45
Also, at u'(0) = 0;
0 = - 8c1 sin 0 + 8c2 cos 0 - (7)(48/45)sin 0
8c2 = 0 and c2 = 0
Thus, the general solution of u(t) is;
U(t) = (48/45)( cos 7t - cos 8t) seconds